دور الإدارة بالقيم في خلق القيمة في المؤسسة: دراسة حالة المؤسسة الجزائرية لصناعة الأنابيب بغرداية / الجزائر - مصيطفى, عبد اللطيف; أرحاب, وسام (University of Eloued جامعة الوادي, 2016)
جاءت هذه الدراسة بهدف إسقاط الضوء على أهمية الجانب الأخلاقي للإدارة في خلق القيمة للمؤسسة، من خلال إبراز تأثير منهج الإدارة بالقيم على أبعاد خلق القيمة، وذلك بتحليل العلاقة بين تطبيق الإدارة بالقيم في المؤسسة وتوفير عوامل خلق القيمة في المؤسسة محل دراستنا – المؤسسة الجزائرية لصناعة الأنابيب. ولقد توصلت الدراسة إلى وجود علاقة ارتباط قوية بين مبادئ الإدارة بالقيم وعوامل خلق القيمة في المؤسسة، كما أن ضعف توجه المؤسسة محل دراستنا نحو الالتزام الأخلاقي في الإدارة أثر سلبا على خلق القيمة. Abstract: This study aims to highlight the importance of the moral side of the management in creating value for the organization, by highlighting the impact of management approach values on the dimensions of value creation, through the relationship between the application of the management by values in the organization and provision of factors of value creation in the enterprise analysis replace our study - ALFAPIPE, using a questionnaire as a tool for the study. The study found a strong correlation between the principles of management by values and factors of value creation in the organization relationship , and the weakness of the institution went replace our study about the moral obligation in the administration negatively impact on value creation .
Value creation by Management Based on Values (MBV) -ALFAPIPE case study
مقال بمجلة رؤى اقتصادية
Keywords: خلق القيمة، إدارة بالقيم، مسؤولية اجتماعية، قِيَم (أخلاق; value creation, management by values, social responsibility, values (ethics).